Estimating operational costs for enhanced continuity in water supply and sanitation services: An inverse data envelopment analysis approach in Chilean utilities - Manuel Mocholi-Arce; Alexandros Maziotis; Ramón Sala-Garrido; María Molinos-Senante (Journal of Hydrology: Regional Studies)
Study region: The largest 23 water utilities in Chile providing water and sanitation services to 97.9 % of total urban customers. Study focus: This study introduces an innovative methodological framework based on inverse data envelopment analysis technique to quantify the additional operational costs required for water utilities to enhance their water supply and sanitation continuity while maintaining their techno-economic efficiency. This framework is pivotal for setting realistic continuity targets and assessing potential impacts on water and sanitation tariffs, thereby aiding in policy and operational planning within the water sector. New hydrological insights for the region: The analysis was performed across four distinct continuity scenarios revealing substantial cost variability contingent on continuity targets, current service levels, and the efficiency of each utility. Results showed a median operational cost increase that varied from 28.41 % in the most stringent scenario to just 0.27 % in the most lenient. The financial implications of meeting these costs through water and sanitation tariffs would necessitate a median monthly increase in water bills, ranging from $17.24 per household in the most demanding scenarios to only $0.01 per household in the more lenient scenarios. This research provides a valuable tool for water sector regulators and managers, enabling informed decision-making by balancing service improvement objectives with economic considerations and customer willingness to pay for enhanced service continuity.